PENYULUHAN PEMBERDAYAAN MASYARAKAT MELALUI MEDIA PAVING BLOCK GUNA MENUNJANG AKSESIBILITAS MASYARAKAT: Desa Bontomanai, Kecamatan Rilau Ale Kabupaten Bulukumba, Sulawesi Selatan - wulansari, indriaty (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Paving block is a building material composition made up of a mixture of portland cement or other hydraulic adhesives, water and aggregates with or without other additives that do not reduce the quality of the concrete (SNI 03-0691-1996). Paving block is a type of precast concrete product. This activity tries to provide information on the importance of adequate infrastructure and an introduction to how make paving block starting from choosing raw materials to make molds to choosing maerials for making concrete block (paving block) to support the accessibility of local people’s or can be used as a place to find income if anyone is interested in starting this material procurement business. Health protocols as a result, the antusiasme of the community who took part in this counseling was very positive, as seen from the many questions and curiosity of the extention participants regarding the materials and tools that would be used if they want to open a community based home based business/industry. For this long periode of time, it is hope that there will be support from the local government so that this activity can be carried out again by involving more people (after the corona pandemic subsides).